Caries experience, periodontal disease and salivary antioxidants as biomarkers of cardiometabolic syndrome among hospital attendees in a Nigerian suburban setting - Adeniyi Oluwadaisi; Oluwadare Ogunlade; Foluso Owotade; Elijah Olufemi Oyetola; Adetayo Aborisade; Asafa Muritala Abiola (BMC Oral Health)
Abstract Background Despite the interconnectedness of oral health and the cardiometabolic syndrome (CMS), the role of oral parameters in diagnosing and predicting CMS risk has been underexplored, particularly in African populations. This study aims to investigate the relationships between oral parameters and CMS risk as a noninvasive means of screening and diagnosis. Methods The study utilized an observational study design. Oral health parameters, anthropometry indices, blood pressure profiles and laboratory indicators of adults with CMS were compared with healthy controls. The relationships of the dental caries, periodontal index, neck circumference, salivary oxidative index of Ferric-Reducing Antioxidant Power (FRAP) and uric acid with variables related to cardiometabolic syndrome in the study group and controls were analyzed. Results Besides height of respondents, all anthropometric variables of weight, BMI, neck and waist circumference were significantly higher in the CMS group (p < 0.001). Saliva pH in CMS participants at 6.90 was significantly lower than the pH of the control group at 7.00 (p = 0.018) while the salivary uric acid level in the CMS group at 4.14 was significantly greater than in “Control” group at 3.06 (p = 0.018). The mean salivary FRAP was significantly greater in the saliva of CMS subjects than in controls (p < 0.001). Similarly, there were also significant differences between the median serum uric acid values(p = 0.002) and serum FRAP scores (p < 0.001). The mean Decayed, Missing and Filled Teeth (DMFT) value for CMS was significantly higher at 1.04 ± 1.13 than that of controls at (0.43 ± 0.73) (p < 0.001) while the Periodontal Inflamed Surface Area (PISA) were also significantly higher (p < 0.001) in CMS patients at 169.43 ± 91.71 mm2 compared to controls (62.28 ± 38.23 mm2). Regression analysis showed salivary, and serum FRAP had odds ratio of 2.39 and 5.39 respectively. Conclusion In this study, dental caries was significantly associated with cardiometabolic syndrome. Similarly, the periodontal inflamed surface area index was positively associated with the CMS compared with the control. Salivary and serum oxidative stress (uric acid and FRAP) values were significantly related in patients with CMS compared with controls. The study concluded that oral health parameters and anthropometric parameters can be excellent noninvasive tools for assessing cardiometabolic risk in community medical and dental practice.